(untitled) (Journal of Nepal Geological Society, 1983)
The stromatolitic phosphorites are found for the first time in the Lesser Himalayan carbonate formations of Far Western Nepal. The phosphorites are confined to the cherty dolomite member which is a part of a thick succession of slate, limestone and dolomite. This paper deals with the petrography of the stromatolitie phosphorite and their chemical composition. The shallow marine environment of phosphate deposition is indicated.